A Rapid Assessment of Knowledge, Attitudes and Practices of Mothers and Caregivers on Childhood Diarrhoea in Unguja, Zanzibar (Tanzania Medical Journal, 2025)
BackgroundChildhood diarrhoea is the third cause of admission and deaths with overall incidence remaining unacceptably high while knowledge, attitude and practices (KAP) of the mothers present affecting vitality of the childhood in most affected communities of Tanzania. Some of the intrinsic and extrinsic factors are age of the mother, knowledge of the causes of diarrhoea, safe stool disposal, mother’s hand washing and subsequent changing of children’s diapers. Therefore, this study aimed at assessment of knowledge, attitudes and practices of mothers and caregivers on childhood diarrhoea in Unguja, ZanzibarMethodsA cross-sectional study conducted from October, 2019 to February, 2020. Twenty-four health facilities were selected from west urban region of Zanzibar in Tanzania. A total of 384 mothers and caregivers with diarrhoea in children under-five years were enrolled. Information on socio-demographic characteristics was obtained by asking the parents/guardians. A questionnaire was administered to the participant. Data were analysed using Statistical Package for Social Science (SPSS) software (16.0 version). Descriptive statistics in frequencies and proportions were used to summarize the information collected. The multivariable analysis was used to assess a rapid assessment of knowledge, attitudes, and practices of mothers and caregivers on childhood diarrhoea whereby p < 0.05 was considered statistically significant.ResultsA total of 384 mothers and caregivers were studied. From the respondents 365(95%) had satisfactory level of knowledge on childhood diarrhoea while 20 (5%) had unsatisfactory knowledge. A total of 196 (51%) rejected the use of Oral Rehydration Solution (ORS) at home due to taste and smell and 188 (49%) agreed on its use. Collectively mothers and caregivers 177 (46%) reported drinking treated or boiling water. A total of 181 (47%) respondents reported hand washing after helping children with defecation while only 73 (19%) respondents reported washing hands before preparing food.ConclusionLimited use of water sanitation and hygiene (WASH) practices was observed among mothers and caregivers of under- five in the prevention and management of childhood diarrhoea. Therefore, there is a need to endorse effective community health education, dissemination of information and community conversations to create a positive practice towards moving knowledge into WASH practices.